The early days of the group of 77 - Karl P. Sauvant (UN Chronicle, 2014)
In December 1961, the United Nations General Assembly designated the 1960s as the “United Nations Development Decade”. At the same time, it also adopted a resolution on “International Trade as the Primary Instrument for Economic Development”, in which the United Nations Secretary-General was asked to consult governments on the advisability of holding an international conference on international trade problems. These resolutions led to the United Nations Conference on Trade and Development (UNCTAD). Their underlying developmental model—trade as the motor of development—shaped the outlook and approach of the new institution.